Efficacy of Dose-Escalated Radiotherapy for Recurrent Colorectal Cancer - Jo, Sunmi; Choi, Yunseon; Park, Sung-Kwang; Kim, Jin-Young; Kim, Hyun Jung; Lee, Yun-Han; Oh, Won Yong; Cho, Heunglae; Ahn, Ki Jung (Annals of coloproctology, 2016)
This study aimed to evaluate the effects of radiotherapy (RT) on progression-free survival (PFS) for patients with recurrent colorectal cancer. We reviewed the records of 22 patients with recurrent colorectal cancer treated with RT between 2008 and 2014. The median radiation dose for recurrent disease was 57.6 Gy (range, 45-75.6 Gy). Patients were divided into 2 groups according to the type of RT: patients underwent RT without previous history of irradiation (n = 14) and those treated with secondary RT (reirradiation: n = 8) at the time of recurrence. The median follow-up period was 24.9 months (range, 4.5-66.6 months). Progression was observed in 14 patients (including 8 with loco-regional failure and 9 with distant metastases). Distant metastases were related to the RT dose (<70 Gy, P = 0.031). The 2-year loco-regional control (LRC), PFS, and overall survival (OS) rates were 74.6%, 45.1%, and 82.0%, respectively. The LRC rate was not different between the patients treated with RT for the first time and those treated with reirradiation (P = 0.101, 2-year LRC 79.5% vs. 41.7%). However, reirradiation was related to poor PFS (P = 0.022) and OS (P = 0.002). An escalated RT dose (≥70 Gy) was associated with a higher PFS (P = 0.014, 2-year PFS 63.5% vs. 20.8%). Salvage RT for locally recurrent colorectal cancer can be offered when surgery is impossible. Dose-escalated RT shows a possible benefit in reducing the risk of progression.